2010
DOI: 10.1128/mbio.00112-10
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B 6 Is Required for Full Motility and Virulence in Helicobacter pylori

Abstract: Despite recent advances in our understanding of how Helicobacter pylori causes disease, the factors that allow this pathogen to persist in the stomach have not yet been fully characterized. To identify new virulence factors in H. pylori, we generated low-infectivity variants of a mouse-colonizing H. pylori strain using the classical technique of in vitro attenuation. The resulting variants and their highly infectious progenitor bacteria were then analyzed by global gene expression profiling. The gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
50
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 42 publications
3
50
1
Order By: Relevance
“…Recently, it has been shown that the vitamin B 6 biosynthesis is essential for virulence of M. tuberculosis (17) and H. pylori (16). However, in our mouse infection experiment, the ⌬pdxS mutant only showed a moderate attenuation and is not statistically significant.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Recently, it has been shown that the vitamin B 6 biosynthesis is essential for virulence of M. tuberculosis (17) and H. pylori (16). However, in our mouse infection experiment, the ⌬pdxS mutant only showed a moderate attenuation and is not statistically significant.…”
Section: Discussioncontrasting
confidence: 48%
“…However, these pathways have not been efficiently explored in pathogenic bacteria. In Helicobacter pylori, it was reported that the DXP-dependent vitamin B 6 biosynthesis pathway plays a role in optimal bacterial growth, chronic colonization of mice, glycosylated flagellum synthesis, and flagellum-based motility (16). The DXP-dependent vitamin B 6 biosynthesis pathway of Mycobacterium tuberculosis is essential for its survival and virulence (17).…”
mentioning
confidence: 99%
“…Two Gram-positive human-pathogenic bacteria, Mycobacterium tuberculosis and Streptococcus pneumoniae, are known to have a DXP-independent de novo vitamin B 6 pathway, which is required for growth in vitamin B 6 -free medium and host colonization in the mammalian model (31,32). Two Gram-negative pathogenic bacteria, Helicobacter pylori and Campylobacter jejuni, are known to have a DXP-dependent de novo B6 pathway, and the role of PLP as a cofactor for a virulence-related enzyme is partially understood (30,33). In H. pylori, PLP is a cofactor that aids PseC's aminotransferase activity.…”
Section: Discussionmentioning
confidence: 99%
“…PLP is known as a cofactor for more than 140 enzymes (21,22) and has been recently considered a virulence factor (30)(31)(32)(33). Two Gram-positive human-pathogenic bacteria, Mycobacterium tuberculosis and Streptococcus pneumoniae, are known to have a DXP-independent de novo vitamin B 6 pathway, which is required for growth in vitamin B 6 -free medium and host colonization in the mammalian model (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins exhibiting the greatest differences in abundance are listed in Table 1. Specifically, the two HSO strains (HSO123 and HSO1) produced higher levels of catalase (37), an iron-regulated outer membrane protein reported to bind heme and hemoglobin (FrpB1 [38,39]), an iron-dicitrate transport protein (FecA1 [40]), and a protein involved in vitamin B 6 biosynthesis (PdxA; 4-hydroxythreonine-4-phosphate dehydrogenase [41]) than the input and RSO strains. Concordant with the results obtained at the protein level, the katA, frpB1, fecA1, and pdxA transcript levels were significantly higher in HSO1 and HSO123 than in RSO241, RSO242, and the input strain (P Ͻ 0.05) (Fig.…”
Section: Figmentioning
confidence: 99%